2014
DOI: 10.1186/1754-6834-7-115
|View full text |Cite
|
Sign up to set email alerts
|

A novel thermostable xylanase GH10 from Malbranchea pulchella expressed in Aspergillus nidulans with potential applications in biotechnology

Abstract: BackgroundThe search for novel thermostable xylanases for industrial use has intensified in recent years, and thermophilic fungi are a promising source of useful enzymes. The present work reports the heterologous expression and biochemical characterization of a novel thermostable xylanase (GH10) from the thermophilic fungus Malbranchea pulchella, the influence of glycosylation on its stability, and a potential application in sugarcane bagasse hydrolysis.ResultsXylanase MpXyn10A was overexpressed in Aspergillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 37 publications
3
35
0
8
Order By: Relevance
“…The cellulose binding and hydrolyzing activity gave ATXX an advantage when reacting with the natural complex substrate, such as wheat bran, corn cob and straw. Ribeiro et al [5] reported that the recombinant thermophilic and thermotolerant Malbranchea pulchella xylanase hydrolyzed pretreated sugarcane bagasse and released the reducing sugar with high concentration. The wheat bran insoluble xylan was hydrolyzed to a mixture of XOs (X2-X6) with relatively high concentration of X3, X4, and X5 by immobilized ATXX (Fig.…”
Section: Hydrolysis Of Wheat Bran Insoluble Xylan and Wheat Bran By Imentioning
confidence: 99%
See 1 more Smart Citation
“…The cellulose binding and hydrolyzing activity gave ATXX an advantage when reacting with the natural complex substrate, such as wheat bran, corn cob and straw. Ribeiro et al [5] reported that the recombinant thermophilic and thermotolerant Malbranchea pulchella xylanase hydrolyzed pretreated sugarcane bagasse and released the reducing sugar with high concentration. The wheat bran insoluble xylan was hydrolyzed to a mixture of XOs (X2-X6) with relatively high concentration of X3, X4, and X5 by immobilized ATXX (Fig.…”
Section: Hydrolysis Of Wheat Bran Insoluble Xylan and Wheat Bran By Imentioning
confidence: 99%
“…Endo-␤-1, 4-xylanase (EC 3.2.1.8, further referred to as xylanase) is one of the important enzymes involved in the degradation of xylan, which is the most abundant natural cell wall polysaccharide after cellulose [1][2][3]. In past 20 years, xylanase has drawn considerable research interest mainly because of its known and potential application, such as production of xylooligosaccharides (XOs) in the food industry and conversion of agricultural by-product into reducing sugar [4][5][6][7]. These applications need enzymes to retain high activity after being used several times at drastic process conditions (high temperature, high ion concentration, acidic, or alkaline environment) and to easily recover from reaction mixtures for reuse.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharification of the agricultural residues by apt pretreatment and enzymatic hydrolysis is of great significance for production of various commercial products [1,3,9,12]. Enzymatic hydrolysis of wheat straw pretreated with dilute alkali and acid with crude xylanase from Aspergillus tubingensis JP-1 yielded 688 and 543 mg/g reducing sugar, respectively [29].…”
Section: Assessment Of a Terreus S9 Xylanase For Hydrolysis Of Rice mentioning
confidence: 99%
“…Being an heteropolysaccharide xylan requires several enzymes for its complete breakdown but endo b-(1,4)-xylanase or simply xylanase (EC 3.2.1.8), is the main enzyme which cleaves the internal b-(1,4)-linked Dxylosyl glycosidic bonds in heteroxylan [6,7]. Xylanases may have application potential for several biotechnological processes such as pulp and paper industries for biobleaching, nutrition-rich animal feed production, bioconversion of LB into simple sugars that can be fermented to produce bioethanol/butanol (biofuel), xylitol, and a variety of other platform chemicals/materials of commercial importance [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation